Modification Weight Criteria With Webbed Model For Selection Artist Music Festival Using Analytical Hierarchy Process (AHP) - I Gede Iwan Sudipa; Putu Sugiartawan; I Komang Arya Ganda Wiguna (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2022)
The process of selecting from many alternatives to the criteria is a decision that is often determined in decision making. The criteria for which criteria can consist of many attributes are used by decision-makers in making the selection or are called multi-criteria decision making (MADM ). Determining the Artist Music Festival at an event has quite a complicated difficulty, because the assessment of the criteria is heterogeneous. The spider web's approach to integrating criteria results in the selection of the artist form that attracts the most attention, and public interest. Model AHP use of multi-attributes is used in selecting artists to perform at music festivals, selecting artists using criteria, namely Number of Followers (C1), stamp C2, Average Popular Tracks (C3), Average Youtube Viewers (C4), and the price of the artist (C5). Data on the number of followers, popularity, average popular tracks, and average YouTube viewers were obtained using the Spotify and Youtube APIs. The settlement method applied is the Analytical Hierarchy Process (AHP) and the Rating Scale algorithm, with an alternative using five samples of Indonesian artists. The research results are expected to provide recommendations for artists as performers in the music festival.